Changes in the expression of molecular genetic regulators of the functional state of endocrine cells in SHR rats - Ivanenko, T. (Journal of Education, Health and Sport, 2024)
Essential arterial hypertension is accompanied by chronic vascular and neurohumoral stress and microcirculatory disturbances that can alter the functional state of the endocrine compartment of the pancreas and promote its remodelling. The molecular mechanisms underlying these changes under conditions of hereditary hypertension remain insufficiently defined, particularly with respect to the involvement of vasoactive, inflammatory, and hypoxia-associated gene networks. In this context, SHR rats represent a relevant model of hereditary hypertension for a systematic assessment of expression changes in key hypertension-related genes in pancreatic tissue. The aim of the work: to determine changes in the expression of key molecular and genetic regulators that characterise the functional state of pancreatic endocrine cells in SHR rats under conditions of hereditary hypertension. Materials and methods. For the analysis of gene expression, the real-time reverse transcription polymerase chain reaction method was used using the PARN-037Z RT² Profiler™ PCR Array Rat Hypertension (QIAGEN, Germany), where the pancreas was the object of the study in experimental animals. Results. In SHR rats, pancreatic tissue showed a coordinated increase in the expression of neurohumoral and vasoactive genes, including Ren (8.87-fold), Agtr2 (4.96-fold), Ece1 (3.42-fold), Ednra (4.65-fold), and Avpr1b (8.10-fold) (2⁻ΔΔCt), indicating activation of local renin-angiotensin, endothelin, and vasopressin-related pathways. A hypoxia-associated response was evident, with Hif1a upregulated 5.37-fold. Marked dysregulation of ion handling and calcium signalling was observed (Kcnj8 2.08-fold, Kcnma1 5.16-fold, Cngb1 5.30-fold, Itpr3 3.59-fold, P2rx4 5.51-fold), accompanied by activation of cytoskeletal and contractile regulators (Mylk 3.01-fold, Mylk2 6.69-fold). Stress-related neuropeptide systems were strongly induced (Calca 6.34-fold, Nppb 196.15-fold), while arachidonic acid-related inflammatory and vasoactive pathways increased (Ptgs1 2.34-fold, Ephx2 8.80-fold) together with metabolic transport changes (Slc7a1 15.47-fold) (2⁻ΔΔCt). Collectively, these shifts support a pattern of chronic neurohumoral overload, hypoxia, ionic and metabolic dysregulation in the pancreas under hereditary hypertension. Conclusions: 1. In SHR rats, increased expression of Ren, Agtr2, Ece1, Ednra, and Avpr1b indicates pathological activation of local neurohumoral systems (renin-angiotensin, endothelin, and vasopressin signalling), which is associated with vasoconstriction, impaired microcirculation, and reduced perfusion of the islets of Langerhans. Upregulation of Hif1a indicates the development of chronic tissue hypoxia in the pancreas under long-term hypertension, creating an unfavourable microenvironment and potentially reducing glucose-stimulated insulin secretion. Increased expression of ion channel and calcium signalling genes (Kcnj8, Kcnma1, Cngb1, Itpr3, P2rx4), together with cytoskeletal and contractile regulators (Mylk, Mylk2), reflects disorganisation of ion homeostasis and exocytosis, which may contribute to calcium overload and endocrine cell dysfunction. Activation of stre ss-related and pro-inflammatory, vasoactive pathways (Calca, Nppb, Ptgs1, Ephx2, Slc7a1) is consistent with metabolic overload and inflammatory, oxidative, and nitrosative stress, thereby amplifying the damaging effects of chronic arterial hypertension and reducing the reserve capacity of the endocrine compartment.